IMPLEMENTATION OF THE NETWORK VULNERABILITY SCANNER ARMITAGE FOR SECURITY WEAKNESSES DETECTION IN THE COMPUTER NETWORK AND SYSTEMS: IMPLEMENTATION OF THE NETWORK VULNERABILITY SCANNER ARMITAGE FOR SECURITY WEAKNESSES DETECTION IN THE COMPUTER NETWORK AND SYSTEMS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper implementation of the network vulnerability scanner Armitage for security weaknesses detection in the computer networks and systems is made.